Malignant Transformation Six Months after Removal of Intracranial Epidermoid Cyst: A Case Report - Fayçal Lakhdar; El Mehdi Hakkou; Rachid Gana; Rachid My Maaqili; Fouad Bellakhdar (Case Reports in Neurological Medicine)
Intracranial epidermoid cysts are uncommon benign tumors of developmental origin; malignant transformation of benign epidermoid cysts is rare, and their prognosis remains poor. We report a case of squamous cell carcinoma arising in the cerebellopontine angle. A 52-year-old man presented with left facial paralysis and cerebellar ataxia. He had undergone total removal of a benign epidermoid cyst six months previously. Postoperative magnetic resonance imaging of the brain revealed a heterogeneous and cystic lesion in the left cerebellopontine angle with hydrocephalus. The cyst wall was enhanced by gadolinium. He underwent ventricle-peritoneal shunt and removal again; the histopathological examination revealed a squamous cell carcinoma possibly arising from an underlying epidermoid cyst. This entity is being reported for its rarity. The presence of contrast enhancement at the site of an epidermoid cyst combined with an acute, progressive neurological deficit should alert the neurosurgeon to the possibility of a malignant transformation.